Use of viral vectors for the development of vaccines. (April 2007) - Liniger, Matthias; Zuniga, Armando; Naim, Hussein Y
The exceptional discoveries of antigen/gene delivery systems have allowed the development of novel prophylactic and therapeutic vaccine candidates. This review highlights various antigen-delivery systems, particularly viral vectors, and assesses the underlying technologies in light of their use against AIDS and malaria. Although such recombinant vectors may face extensive preclinical testing and will possibly have to meet stringent regulatory requirements, some of these vectors may benefit from the profound industrial and clinical experience of the parent vaccine. Most notably, novel vaccines based on live, recombinant vectors may combine the induction of broad, strong and persistent immune responses with acceptable safety profiles.